Examining regional variability in work ethic within Mexico: Individual difference or shared value. (19th February 2018) - Arciniega, Luis M.; Woehr, David J.; Del Rincón, Germán A.
Abstract : Despite the acceptance of work ethic as an important individual difference, little research has examined the extent to which work ethic may reflect shared environmental or socio‐economic factors. This research addresses this concern by examining the influence of geographic proximity on the work ethic experienced by 254 employees from Mexico, working in 11 different cities in the Northern, Central and Southern regions of the country. Using a sequence of complementary analyses to assess the main source of variance on seven dimensions of work ethic, our results indicate that work ethic is most appropriately considered at the individual level.